A Simple Imaging Guide for Endovascular Thrombectomy in Acute Ischemic Stroke: From Time Window to Perfusion Mismatch and Beyond - Yu, Wengui; Jiang, Wei-Jian (Frontiers in Neurology, 2019)
In 2015, 5 randomized controlled trials (RCTs) independently demonstrated the safety and efficacy of EVT for AIS from large vessel occlusion (LVO) in the anterior circulation within 6-12 hours of symptom onset, a result later confirmed by 3 other trials. In early 2018, 2 additional RCTs extended the time window to 16-24 hours. However, there were great variabilities in the use of imaging tools for patient selection in the RCTs. The goal of this review is to appraise the imaging modalities used in the landmark studies and to propose a simple and efficient imaging protocol for patient selection in the real-world practice. Non-contrast computed tomography (CT) and CT angiography (CTA) were used for patient selection in 8 of the 10 recent RCTs. Initial infarct volume was assessed using Alberta Stroke Program Early CT Score (ASPECTS) on non-contrast CT. LVO and collaterals were screened with CTA. In contrast, advanced imaging modalities, including CT perfusion and diffusion/perfusion MR imaging, were used to evaluate infarct core and ischemic penumbra in EXTEND-IA, SWIFT PRIME, DAWN and DEFUSE 3 trials. These landmark studies demonstrated the best treatment effect and extended time window for EVT. However, they only selected patients with small infarct core per perfusion/diffusion imaging and have excluded patients who could benefit from EVT. In addition, advanced imaging tools are not widely available in developing regions and the time spent on acquiring and processing the perfusion/diffusion imaging may cause delay in reperfusion therapy. The perfusion/diffusion imaging can also overestimate the infarct core. Recent studies reported that a significant proportion of DAWN- and DEDUSE 3- ineligible patients can benefit from EVT. Among the 10 RCTs, 8 used ASPECTS score for patient selection and independently demonstrated the benefit of EVT. As confirmed by DAWN trial, a mismatch between clinical deficit and infarct is the key indication for EVT. A simple imaging protocol to identify clinical-imaging mismatch from LVO appears to be the best guide for EVT in clinical practice. Perfusion imaging should be considered in patients without clinical-imaging mismatch.